Analisis Kemampuan Komunikasi Matematis Siswa SMP Kelas VIII pada Materi Relasi dan Fungsi - Witri Mulyanti Witri; Adi Ihsan Imami (Didactical Mathematics, 2022)
This research aims to analyze and describe the mathematical communication skills of junior high school students in grade VIII on relationship and function materials in one of the schools in Karawang Regency. The type of research used is qualitative descriptive research with a total of 3 subjects. The taking of the subject is done using purposive sampling techniques. The instrument used in this study is a written test with the number of essay problems as many as 6 questions that contain 3 indicators of mathematical communication skills, namely: 1.) Linking images, tables, graphs into mathematical ideas. 2.) Stating everyday events into a language or mathematical symbol 3.) Provide explanations, ideas, concepts, or mathematical situations with their own language in written form. Instrument results are categorized into 3 categories, namely low, medium, and high. The results of the analysis of mathematical communication skills as a whole are relatively low with a percentage of 32.22%. There is one indicator that includes the medium criterion and two indicators that include the low criterion. Students who have high mathematical communication skills can master all three indicators of mathematical communication skills. Students who have medium mathematical communication skills can only master two indicators of mathematical communication skills. While students who have low mathematical communication skills cannot meet all three indicators of mathematical communication skills.